2017
DOI: 10.4103/1119-3077.197020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of calcium silicate cement bond strength after using gutta-percha solvents

Abstract: Gutta-percha solvents used during retreatment decreased the bond strength of Biodentine and CMTA to root dentin. The bond strength of WMTA was not affected by the use of gutta-percha solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…Most studies demonstrated statistically significant differences in dislodgment resistance after the use of a chelating solution in comparison to control groups, except for one (34). Three studies (33,35,40) showed no differences among the chelating groups tested. In one of the studies (35), the chitosan presented higher values of dislodgment resistance than 17% EDTA and Smear Clear ® and demonstrated that QMix and 17% EDTA had similar effects on the bond strength of all the sealers tested.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Most studies demonstrated statistically significant differences in dislodgment resistance after the use of a chelating solution in comparison to control groups, except for one (34). Three studies (33,35,40) showed no differences among the chelating groups tested. In one of the studies (35), the chitosan presented higher values of dislodgment resistance than 17% EDTA and Smear Clear ® and demonstrated that QMix and 17% EDTA had similar effects on the bond strength of all the sealers tested.…”
Section: Resultsmentioning
confidence: 95%
“…Three studies (33,35,40) showed no differences among the chelating groups tested. In one of the studies (35), the chitosan presented higher values of dislodgment resistance than 17% EDTA and Smear Clear ® and demonstrated that QMix and 17% EDTA had similar effects on the bond strength of all the sealers tested. Güzel et al .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations